Microemulsion-based palm kernel oil extraction using surfactant solution - Nor Bainun, Binti Ismail (Universiti Malaysia Sarawak, UNIMAS, 2012)
Vegetable oils have been used widely as raw material for biodiesel production. The usage of solvent extraction with hexane is not favorable due to adverse effect to human and environment. In this study, microemulsion-based extraction of palm kernel oil using nonionic surfactant Brij-30 was used as an alternative method to replace solvent extraction. The quality of oil extracted by solvent and microemulsion-based extractions was also compared. Dried and ground palm kernel (0.2-0.5 mm) was shaken with surfactant on rotary shaker at 150 rpm for every parameter. Parameters that were studied to find the optimum oil extraction conditions are weight of sample, surfactant concentration, contact time and temperature. Once the optimum conditions were obtained, solvent extraction was done for comparison. Physical appearances, extraction efficiency and Fourier Transform Infrared (FTIR) characterization for both extractions were compared. Based on the result obtained, optimum conditions for microemulsion-based extraction are 30 minutes contact time, 1g weight of sample, 0.015 M surfactant concentration and room temperature 25 oC. Extraction efficiency by using solvent yield highest oil, 88.5% compared to microemulsion-based extraction, 59.2%.